From second webspace syndrome to second cross over toe: Clinical and radiological findings following Weil osteotomy with no soft tissue procedure. Issue 2 (February 2023) - Sallent, Andrea; Methol, Geronimo; Altayo, Marta; Soza, Diego; Duarri, Gemma; Maled, Ignacio; Busquets, Rosa
Abstract: Background: The second webspace syndrome (SWS) refers to the progressive divergence between 2nd and 3rd toes associated with pain at the second intermetatarsal space that can be confused with Morton's neuroma and treated as such without considering the underlying deformity. There is yet no consensus regarding the best treatment, from isolated soft tissue or bony procedures or a combination of both. The objective of this study was to describe the clinical characteristics of the disease, as well as to evaluate the radiological outcomes of patients with SWS treated with open Weil's osteotomy or distal metatarsal minimal invasive osteotomy (DMMO) of the second metatarsal, with main emphasis on medialization of the head in the anteroposterior plane in either procedure. Methods: A retrospective study of all patients with SWS treated with Weil's medializing osteotomy (open and percutaneous) associated or not with other forefoot procedures, treated between 2012 and 2019, was performed. Radiological variables such as metatarsal-phalangeal angle (MTPA), percentage of metatarsal uncoverage of M2 with respect to its phalanx, intermetatarsal angle (M1, M2 and M3), length of second metatarsal and intermetatarsal distance M2 - M3 were measured and compared before and after surgery. Results: Twenty-six patients were included, with a mean follow-up of 26 months. All patients presented divergence between the 2nd and 3rd toes, 75 % associated pain at the level of the second intermetatarsal space and two patients presented neuropathic symptoms. After surgery (nineteen open and seven DMMO), all patients rated their results as good or excellent, and the two patients with neuropathic symptoms had improvement in their symptoms. Regarding the radiological results, the percentage of subluxation of the second MTP decreased in a large percentage of the operated patients (from 43.3 % to 3.9 %) with statistical significance as well as the length of M2, IM angle between M1 - M2, IM distance between M2-M3 and the percentage of uncoverage of the second MTP (p < 0.001). Conclusion: Medial translation associated with open Weil osteotomy or DMMO seems to correct the muscle-ligament imbalance of the second metatarsophalangeal joint and restore normal radiographic measurements, especially in the coronal and sagittal plane, without the need for soft tissue procedures, as well as the resolution of associated neuropathic symptoms in some patients. Level of evidence: Level IV, retrospective case series